Neuroimaging through Sonolucent Cranioplasty: A Systematic Scoping Review Protocol - Christina P. Rossitto; Alex Devarajan; Gabrielle Price; Muhammad Ali; Christopher P. Kellner (Methods and Protocols, 2022)
Cranioplasty is a neurosurgical procedure in which the skull bone is repaired after craniectomy. Recently, studies have suggested that sonolucent synthetic materials are safe and useful for cranioplasty. Sonolucent cranioplasty (SC) implants provide unprecedented opportunity in adult neurosurgery to monitor neuroanatomy, assess hemodynamics, view devices located within the implant, and conduct focused ultrasound treatments. Current research on SC includes proof-of-concept cadaveric studies, patient-related safety and feasibility studies, and case series demonstrating transcranioplasty ultrasonography (TCUS). The purpose of this protocol is to investigate the current literature on SC use and outcomes in TCUS. We will perform a systematic literature search following PRISMA-ScR guidelines. The search will be conducted using Ovid Embase, Ovid Medline, and Web of Science Core Collection databases. Titles, abstracts, and full texts will be screened. Joanna Briggs Institute critical appraisal tools will be utilized. Data extraction points will include subject characteristics, SC implant characteristics, ultrasound characteristics, and sonographic findings. These findings will provide a comprehensive review of the literature on sonolucent cranioplasty and directions for future research.